"FOLK BELETRISTICS" IN THE WORKS OF VOLDOYMYR KOROLENKO AND PANAIT ISTRATI - Yovdiy, V. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article on the material of prose by V. Korolenko and P. Istrati analyzes the form of the narration with the simulation of verbal speech. This type of narrative is oriented to "extra-literary", oral, everyday speech and is dominant in the work of Korolenko and Istrati. For writers, this is a "stranger’s voice" of a certain social type’s representative with a certain spiritual level and worldview, and not just an individual-characteristic image of "classical" rage. There is a refraction of authors’ intentions in the "two-voiced" word of the narrator. The article describes the peculiarity of the writers’ narrative, common and distinctive features of their artistic word, oriented to "folk fiction".